REPUTASI MEREK, KOMPETENSI MEREK, KESUKAAN MEREK DAN KEPERCAYAAN PADA PERUSAHAAN TERHADAP LOYALITAS MEREK APOTEK VITKA FARMA - Dewi Aurora Mikasari; Agung Edy Wibowo (LPPM Universitas Ibnu Sina, 2021)
As a business entity, pharmaceutical companies have a big part in providing a contribution to the growth of a nation; the number of pharmaceutical retail outlets support the strength of a country health system. Apotek Vitka Farma is one of the pharmacies that are existing and provide support to the particular vision. As a business entity Apotek Vitka Farma has a compound competition space with other retails in similar industries. The expectation of winning over potential niche existing customers is a priority in such intense competition. The significant part of the whole process is to change the behavior of consumers in the end to become loyal customers. This research aims to obtain outcomes on the analysis of brand reputation variable, brand competence, brand preferences and consumer’s trust in the company to the loyalty in the brand of Apotek Vitka Farma.The survey with purposive sampling method was used in this study with a sample number of 120 respondents. Classic assumption tests were used to ensure that the Best Linear Unbiased Estimator (BLUE) requirements were met before further testing using multiple linear regression analysis. The results of this study show that brand reputation has a significant influence on the brand loyalty of Apotek Vitka Farma brand. Brand competence has a significant influence on the reliability of Apotek Vitka Farma brand. Brand preference has a significant influence on the brand loyalty of Apotek Vitka Farma brand. Consumer’s trust in the company has a significant influence on the brand loyalty Apotek Vitka Farma brand. Trust in company has dominant influence on the brand loyalty of Apotek Vitka Farma.